THE INFLUENCE OF EFFECTIVENESS IN CREATING DEVELOPMENT ON ORGANIZATIONAL CULTURE - Widiasih, Suprapti (Institut Riset dan Pengembangan Indonesia, 2025)
Organizational culture is the values, norms, and beliefs that are embraced and practiced by members of the organization. Organizational effectiveness refers to the organization's ability to achieve a common goal that has been set. Organizational development is something that cannot be ignored, because if changes are not made, the company cannot continue to exist. The purpose of this study is to find out how significant the success of an effective organizational culture is in building healthy organizational development. The method used is a qualitative method using literature studies. Research shows that a strong organizational culture that conforms to desired values can increase organizational effectiveness. A culture that encourages innovation, collaboration, and high performance is likely to create a productive work environment. Thus, a positive organizational culture can be one of the keys to success in creating organizational development.